Analisis Pembingkaian Kekerasan Seksual di Media Online Times Indonesia dan Tugumalang.id - Yulia Melci Bele; Latif Fianto (Yayasan Lentera Avanya Nagari, 2025)
This study aims to identify and analyze how the reporting of sexual violence by Julianto Eka Putra in the online media Times Indonesia and Tugumalang.id frames the event, as well as how the news elements shape the audience's understanding. This study uses the framing theory of Zhongdang Pan and Gerald M. Kosicki, focusing on the analysis of syntactic, script, thematic, and rhetorical aspects in the news coverage. The method used is qualitative descriptive, with a framing analysis approach to news from both media. The results showed significant differences in the way the two media compiled the news. Times Indonesia did not fully use the 5W+1H news structure, while Tugumalang.id was more consistent in its completeness. Differences are also seen in the choice of words in the headline, where Times Indonesia uses the term “terdakwa” (defendant) and Tugumalang.id chooses “bos” (boss) to refer to the perpetrator. Emphasis on the background of the news and quotes from sources are framing strategies used to shape different narratives. This study concludes that even though both media discuss the same issue, the way they present information and frame events can influence the audience's view of the case. Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis bagaimana pemberitaan kekerasan seksual oleh Julianto Eka Putra di media online Times Indonesia dan Tugumalang.id membingkai peristiwa tersebut, serta bagaimana elemen-elemen berita membentuk pemahaman audiens. Penelitian ini menggunakan teori framing dari Zhongdang Pan dan Gerald M. Kosicki, dengan fokus pada analisis aspek sintaksis, skrip, tematik, dan retoris dalam pemberitaan. Metode yang digunakan adalah deskriptif kualitatif, dengan pendekatan analisis framing pada berita dari kedua media tersebut. Hasil penelitian menunjukkan adanya perbedaan signifikan dalam cara kedua media menyusun berita. Times Indonesia tidak sepenuhnya menggunakan struktur berita 5W+1H, sementara Tugumalang.id lebih konsisten dalam kelengkapan tersebut. Perbedaan juga terlihat dalam pemilihan kata di headline, di mana Times Indonesia menggunakan istilah